2014
DOI: 10.1038/gt.2014.75
|View full text |Cite
|
Sign up to set email alerts
|

High and prolonged sulfamidase secretion by the liver of MPS-IIIA mice following hydrodynamic tail vein delivery of antibiotic-free pFAR4 plasmid vector

Abstract: Mucopolysaccharidosis type IIIA (MPS-IIIA) or Sanfilippo A syndrome is a lysosomal storage genetic disease that results from the deficiency of the N-sulfoglucosamine sulfohydrolase (SGSH) protein, a sulfamidase required for the degradation of heparan sulfate glycosaminoglycans (GAGs). The accumulation of these macromolecules leads to somatic organ pathologies, severe neurodegeneration and death. To assess a novel gene therapy approach based on prolonged secretion of the missing enzyme by the liver, mediated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 45 publications
(61 reference statements)
0
26
0
1
Order By: Relevance
“…In our study, we showed that a long term transgene expression could be obtained using pFAR4 miniplasmids. The advantages of these miniplasmids have been proven in vivo upon hydrodynamic injection thanks to their reduced size, nontoxic and non-immunogenic side effects [22,23]. These features may play a significant role in gene transfer efficiency by sonoporation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, we showed that a long term transgene expression could be obtained using pFAR4 miniplasmids. The advantages of these miniplasmids have been proven in vivo upon hydrodynamic injection thanks to their reduced size, nontoxic and non-immunogenic side effects [22,23]. These features may play a significant role in gene transfer efficiency by sonoporation.…”
Section: Discussionmentioning
confidence: 99%
“…Removal of all or part of bacterial sequences from gene vectors (e.g. in minicircles or in pFAR4 miniplasmids, respectively) allowed to alleviate this silencing effect [22,23]. Alternatively, the use of molecular tools (DNA transposons or integrases) that mediate transgene integration into host genome led, in mice, to high and prolonged therapeutic levels of Factor IX that is deficient in hemophilia B patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…В некоторых исследованиях с использованием вну-тривенного введения аденоассоциированного (AAV8) и лентивирусного векторов, а также других способов доставки гена в клетки печени (гидродинамических инъ-екций плазмид; микроциркулярной ДНК, представля-ющей собой плазмиду, лишенную некоторых бактери-альных последовательностей ДНК; транспозона «спящая красавица», способного к интеграции в геном клеток хозяина) продемонстрирована возможность уменьше-ния степени выраженности патологических изменений не только в соматических клетках, но и в тканях головно-го мозга экспериментальных животных моделей МПС I, IIIА и VII [4,37,38]. По мнению некоторых исследовате-лей, механизм данного явления может быть связан с про-никновением через ГЭБ непрерывно синтезируемого на периферии фермента, преодолением вирусным векто-ром незрелого ГЭБ или несостоятельностью ГЭБ в связи с течением воспалительного процесса у используемых лабораторных животных [8,10].…”
Section: генная терапия In Vivounclassified
“…et al, 2010), ERT(Lee et al, 2011(Lee et al, , 2014Higuchi et al, 2012;Hong et al, 2012;Sohn et al, 2018 Sohn et al, ) et al, 2007Haurigot et al, 2013), AI(Arfi et al, 2011), BMT(Lau et al, 2012),LV (McIntyre et al, 2008), SRT(Roberts et al, 2010) Mgat3 (D31N)(Bhattacharyya et al, 2001) + + AAV(Ruzo et al, 2012;Haurigot et al, 2013), ERT(Gustavsson et al, 2019), GT(Quiviger et al, 2014), SRT(Roberts et al, 2007) Mgat3(CKO) (Lau et al, 2017(Lau et al, ) et al, 2004Ribera et al, 2015), ERT(Kan et al, 2014),LV (Di Natale et al, 2005Blanz et al, 2008;Damme et al, 2011) NEU1 Sialidosis, Type I & II Neu1 (−/−) (de Geest et al, 2002) + < Neu1 (V54M) (Bonten et al, 2013) + + Chaperone-AAV (Bonten et al, 2013)(Continued)…”
mentioning
confidence: 99%